High temperature study of dielectric and electrical conduction behaviour of La2NiO4 - Katheriya T.; Upadhyay S. (My University, 2025)
Materials showing negative permittivity have attracted considerable attention from researchers on account of their notable applications in electronic and electromagnetic devices. Discovering materials exhibiting negative permittivity is a challenging task. Very few single-phase oxides have been reported as negative permittivity materials. In this work, we have attempted to investigate the dielectric properties of La2NiO4 to explore the possibility of negative permittivity. To achieve the goal, powder, and ceramic of La2NiO4 have been synthesized by the conventional solid-state reaction method. Rietveld refinement of the X-ray diffraction data studies has confirmed the tetragonal structure and space group I4/mmm. The Dielectric properties and AC conductivity have been studied in the frequency range of 20 Hz-2 MHz and over a wide temperature range (30 °C-600 °C). The permittivity of La2NiO4 is found to be negative at all the measured frequencies and temperatures. The Drude model fitted the experimental data very well, suggesting that negative permittivity behavior can be assigned to the plasma oscillation of conducting electrons. The trend of AC conductivity with frequency is similar to the skin effect observed in metals. The variation of DC conductivity with temperature indicated small polaron hopping conduction mechanism. Analysis of reactance (Z′′) suggested inductive electrical character in the tested frequency and temperature range. Room temperature negative permittivity behavior of La2NiO4 makes it a potential candidate for practical electronic and electromagnetic devices that work in the Radio-frequency range. Furthermore, this work will add a new member to the family of Perovskite oxides showing tunable negative permittivity. © 2023 IOP Publishing Ltd.